FEASIBILITY ANALYSIS OF THE COMPANY USING SWOT AND PESTEL METHODS - Permatasari, Trisna Ary Vika; Khalid , Zulivia (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The healthy food trend is increasingly popular, driven by increasing public awareness of the importance of a healthy lifestyle. Lite n' Easy, a company that provides healthy food delivery services, ofers a solution for people who want to live healthy but are busy. This research aims to analyze the feasibility of the Lite n' Easy business using the SWOT and PESTEL methods. This research uses a case study method at Lite n' Easy in Brisbane, Australia, for the period March to July 2024. Data was collected through observation and literature study. SWOT analysis is used to assess the company's internal strengths, weaknesses, opportunities and threats, while PESTEL analysis is used to assess external factors such as political, economic, social, technological, environmental and legal factors that influence the company's operations and strategy. Based on SWOT and PESTEL analysis, Lite n' Easy has the opportunity to develop in the healthy food market. However, companies need to overcome several weaknesses and threats to achieve long-term success. Strategies that Lite n' Easy can implement include emphasizing its commitment to providing nutritious and convenient food options, increasing its geographic reach, increasing brand awareness, and adapting to changing externalfactors.